(untitled) (Bangladesh Journal of Zoology, 2019)
A cross sectional study was carried out among school going children of Ganaktuli slum area in Dhaka city, Bangladesh. A total of 183 stool samples were collected from children of age between 5 and 16 years of both sexes during May, 2017 to April, 2018. Collected samples were examined using Formal-Ether Concentration technique. 61.20% samples were found positive for intestinal parasites. Eight species of parasites were identified, where Entamoeba histolytica (3.83%), Giardia lamblia (6.01%), Diphyllobothrium latum (3.28%), Paragonimus westermani (3.83%), Ascaris lumbricoides (24.59%), Trichuris trichiura (12.02%), Ancylostoma duodenale (5.46%) and Enterobius vermicularis (2.19%) was recorded. Male children showed higher (63.95%) prevalence than female (58.76%). The highest and lowest prevalence (82.46 and 39.29%) were found among 8 - 10 and 14 - 16 years children, respectively. The highest prevalence of E. histolytica (7.02%), A. lumbricoides (38.60%), T. trichiura (14.04%) and A. duodenale (8.77%) were observed in 8 - 10 years age group; G. lamblia (7.41%), P. westermani (5.56%) and E. vermicularis (3.70%) in 11 - 13 years age group and D. latum (6.90%) was found highest in 14 - 16 years age group. Statistically it was observed that age groups had significant association with parasitic infestation (p < 0.05) but prevalence did not alter significantly according to sexes (p > 0.05). Highest abundance of parasites was recorded for A. lumbricoides. Bangladesh J. Zool. 47(1): 67-75, 2019